2011
DOI: 10.1590/s1517-83822011000200024
|View full text |Cite
|
Sign up to set email alerts
|

Identification, isolation and optimization of antifungal metabolites from the Streptomyces Malachitofuscus ctf9

Abstract: An indigenous Streptomyces isolate CTF9, exhibiting promising antifungal activity against Mucor mieheiand Candida albicans in pre-screening studies, was investigated by cultivation in a 50-L fermenter and by subsequent isolation, purification, and structure elucidation of the active metabolites. Based on the morphological, biochemical, and physiological characterization, as well as the 16S rRNA gene sequence, the isolate CTF9 was identified as Streptomyces malachitofuscus. Using a series of chromatographic tec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 22 publications
(4 reference statements)
1
11
0
Order By: Relevance
“…The Streptomyces sp. isolated from saline farm-lands showed both antibacterial and antifungal activity (Sajid et al 2009). The antioxidant activity of the VITJS11 crude extract showed maximum activity with 85% inhibition at 5.0 mg/mL concentration and its activity remained highly significant with the reference used (Fig.4).…”
Section: Resultsmentioning
confidence: 99%
“…The Streptomyces sp. isolated from saline farm-lands showed both antibacterial and antifungal activity (Sajid et al 2009). The antioxidant activity of the VITJS11 crude extract showed maximum activity with 85% inhibition at 5.0 mg/mL concentration and its activity remained highly significant with the reference used (Fig.4).…”
Section: Resultsmentioning
confidence: 99%
“…strains isolated from the Japan Sea's sediment, Goodfellow and Fiedler [51] identified atrop-abyssomicin C and proximicins A, B and C. It inhibits the formation of p-aminobenzoate during tetrahydrofolate synthesis in Gram-positive bacteria with methicillin-resistant Staphylococcus aureus (MRSA). The Streptomyces malachitofuscus has anti-fungal action against Candida albicans and Mucor miehei, as Sajid et al [52] reported. The spoxazomicins was extracted from Streptosporangium oxazolinicum sp.…”
Section: The Important Antibiotics Isolated From Actinobacteria Against Drug-resistant Pathogensmentioning
confidence: 90%
“…The genus Streptomyces seems to provide a wide variety of new antibiotics more than any other genus; hence, it is of great importance for both industrial applications and human health care. [40] Optimization of culture conditions…”
Section: Molecular Identificationmentioning
confidence: 99%